Efeito de densidades do solo e doses de calcário no desenvolvimento inicial do pinhão-manso - Ohland, Tatiane (2012)
Two experiments were conducted in a greenhouse in pots made of PVC tubes containing 10.6 dm3 of soil, using a randomized complete block design with four replications. The first experiment aimed to evaluate the influence of soil density in the initial development of physic nut (Jatropha curcas L.). The soil used was an Oxisol clayey, in levels of bulk density of 1.08, 1.22, 1.36, 1.50 and 1.64 kg dm-3. After 120 days of plant emergence, was evaluated the number of leaves, plant height, stem diameter, leaf area, root length, root volume, dry matter of leaves + petioles, stems, roots, total dry matter of plant, root/shoot ratio and the content of P, K, Ca and Mg. The results indicate that the increase of soil density negatively affected the development of shoot and root system of plants of physic nut. The limitation of shoot growth occurred from the estimated density of 1.26 kg dm-3, reducing the number of leaves, leaf area and dry matter of shoots. The root system development and content of P and K in plants of physic nut decreased linearly with increasing density. The contents of Ca and Mg is not influenced by increasing the density of the soil. The second experiment aimed to evaluate the initial development of physic nut in different limestone rates in subsurface. The soil used was Oxisol clayey collected in Cascavel - PR. The physic nut plants were grown in PVC pots divided into two rings, the upper ring (0-20) received limed soil (11.1 t ha-1 of CaCO3 and MgCO3) and fertilized, the lower ring (20-60 cm) was added to soil at doses of 0, 3.7, 5.6, 7.4, 11.1 and 14.9 t ha-1 of CaCO3 and MgCO3 in 4:1 molar ratio. After 120 days of plant emergence, was evaluated the number of leaves, leaf area, plant height, stem diameter, root length, root volume, dry matter of leaves, stems, roots, and total dry matter of plant and levels of Al, P, K, Ca, Mg, Zn, Cu, Mn and Fe in leaves, stems and roots. The development of the shoot of physic nut was not limited by the different limestone rates in subsurface, as assessed by plant height, stem diameter, dry matter of leaves, stem and total dry matter of plant. The decrease in limestone rates reduces the volume and dry matters of roots in subsurface. Liming decreased the concentration of Zn and Mn in shoots and roots, which may have influenced the plant height and root volume